The effect of climbing and descending stairs varies in improving balestra fencing floret/foil weapon type - Amahoru, Musfira; Mahyudin, Reza; Samudro, Touvan; Dahlan, Firmansyah; Idha, Takbiratul (Jurnal Keolahragaan, 2023)
Fencing is a sport that requires a maximum physical component so that in this study the aim was to test and find out the effect of variations in stair climbing exercises in improving floret/foil balestra fencing weapons. This study used a test-experiment with the research design "Single-Group Pretest-Posttest Design". The research sample consisted of 20 people, coming from students (elective course (MKP) Fencing) of a state university in eastern Indonesia (male and female) who were then divided into training groups through random sampling technique. The balestra fence measurement tool for floret/foil type weapons uses the Kuhadja fencing skills test. Pretest and posttest results were analyzed using the influence test (t-test). The research location is at the Football Stadium (a stadium grandstand with 25 steps). Results; 1) there was a significant difference between the pretest and posttest groups with the various stair climbing exercises towards increasing the ability to balestra floret fencing weapons. 2) There is a significant difference between the posttest (after treatment) of varied stair climbing training and the control group in increasing the ability to balestra floret fencing weapons. We estimate that this increase is the result of increased leg muscle strength, speed, and explosive power obtained through varied stair climbing exercises.